Modeling Sludge Accumulation Rates in Lined Pit Latrines in Slum Areas of Kampala City, Uganda - Lugali, Yvonne; Zziwa, Ahamada; Banadda, Noble; Wanyama, Joshua; Kabenge, Isa; Kambugu, Robert; Peter Tumutegyereize (African Journal of Environmental Science and Technology, 2016)
Disposal of faecal sludge particularly in slum areas is a difficult undertaking given the lack of space and resources. Inaccurate prediction of sludge accumulation rates (SAR) in pit latrines leads to unplanned pit latrine emptying. Given that the users and owners cannot afford the conventional emptying techniques frequently, inappropriate methods such as open defecation and emptying into storm drainages are employed which consequently contribute to environmental and health-related challenges. The main objective of this study was to develop a predictive model for sludge accumulation rates in lined pit latrines in slum areas of Kampala so as to guide routine management of pit latrines. This mathematical model was developed using a mass balance approach with a sample space of 55 lined pits. The developed model gave an average sludge accumulation rate of 81±25 litres/person/year with an efficiency of 0.52 and adjusted R2 value of 0.50. The model was found to be sufficient and most suited for rental and public pit latrines given their bigger percentage in the slums. Further studies should include geo-physical characterization of soil and drainage of pit latrine sites so as to improve model accuracy.
Keywords: Faecal, sludge accumulation rates, slum areas, lined pit latrines